Assessing the levels of traffic noise in selected Schools in Bandar Baru Bangi - Hoo, Rui Wen; Mohd Faizal Mat Tahir; Azli Ariffin; Mohd Rasidi Mohd Rasani; Meor Iqram Meor Ahmad; Mohd Zaki Nuawi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Traffic noise during school hours can disrupt students’ learning focus especially in the classroom and can affect communication between teachers and students. This study was conducted to asses traffic noise levels for four selected schools along few main roads in Bandar Baru Bangi and analyse the data using the guideline recommended by the Malaysia Department of Environment (DOE). Data was collected using 01dB SOLO sound level meters using the decibel A-weighted (dBA) for LAeq , L10 , L50 , L90 , LAeqmax dan LAeqmin . The measurement was collected during the respective peak hour on school days which are 7.00am -9.00am for morning session, 12.00pm -2.00pm for noon and 5.00pm -7.00pm for evening session. The measured noise then analysed and compared with the recommended standards set by the DOE. From the measurement, it was found that traffic near the Greenview Islamic International School recorded up to 76.3dB(A) for LAeq, 110.3 dB(A) for LAmax , L10 = 78.4 dB(A) and L90 = 67.6 dB(A) during the period of 12.00pm to 1.00pm. All the measured traffic noise at the respective school also logged a high noise level for their LAeq measurement. In conclusion, the study showed that the traffic noise level pollution experience by the schools along the main roads in Bandar Baru Bangi district were alarming which are exceeding the recommendation from DOE. This finding can help policymakers and stakeholders used as reference in sense of noise pollution management for better acoustics comfort at school area.